CFD analysis on the directional stability and terminal velocity of the OMNI-Max anchor with a booster. (1st January 2019) - Liu, Jun; Ma, Yueyuan; Han, Congcong
Abstract: The OMNI-Max anchor, a newly developed gravity installed anchor, offers a cost effective anchoring solution with improved reliability for deep-water mooring facilities. However, the anchor final penetration depth is relatively shallow in the soil with high strength gradient. A booster, which can be attached at the tail of the OMNI-Max anchor, is designed with the aim to improve both the anchor directional stability and terminal velocity, such that the anchor can penetrate deeper into the seabed and consequently gain higher holding capacity. The objective of this paper is to investigate the directional stability and terminal velocity of the OMNI-Max anchor and hybrid anchor (i.e. an OMNI-Max anchor with a booster) based on the computational fluid dynamics (CFD) approach. The numerical simulation results demonstrated that the booster is beneficial in moving the position of the hydrodynamic centre towards the anchor rear, hence the directional stability of the hybrid anchor is improved. Moreover, the anchor terminal velocity was increased from 22.44 m/s to 32.01 m/s by the aid of a booster. Finally, an optimised design on the booster geometry was performed to ensure that the hybrid anchor can obtain high terminal velocity and maintain directional stability at the same time. Highlights: The hydrodynamic characteristics of OMNI-Max anchor are investigated. The booster structure was optimised to improve both the terminal velocity and directional stability of hybrid anchors. The efficiency of the booster on the terminal velocity of OMNI-Max anchor was investigated.